Transformative reparations?: A critical look at a current trend in thinking about gender : just reparations - Walker, Margaret Urban (International journal of transitional justice, 2016)
Gender justice in reparations for women requires that entrenched oppression or disadvantage suffered by women does not result in women being deprived of recognition as victims and of access to full and effective reparation. An idea has taken hold in both policy and academic inquiry that gender-just reparations should be ‘transformative’ rather than (merely) corrective or restorative. I question the most ambitiously transformative aims that seek to make reparations into an instrument of society-wide structural change. I suggest that this conception not only overreaches practically and politically but that it threatens to bypass or aims to displace reparative justice as a distinct and distinctly victim-centered imperative. In doing so, it demotes the importance of recognizing individual victims themselves, whose status as bearers of rights and subjects of justice depends crucially on their standing to claim accountability and repair for violations to their individual persons.